Surface Analysis of a Universal Resin Composite and Effect of Preheating on its Physicochemical Properties - Manoel da Silva, Marcus Vinicyus; Batista, Joao Marcos Nascimento; Fraga, May Anny Alves; Correr, Americo Bortolazzo; Alves de Campos, Edson [UNESP]; Geraldeli, Saulo; Sinhoreti, Mario Alexandre Coelho (FapUNIFESP (SciELO), 2023)
This study was aimed at analyzing the surface properties of a universal resin composite and evaluating the effect of preheating on its physicochemical properties. Two commercial resin composites were used under two conditions: Filtek Universal Restorative (UR); UR preheated (URH); Filtek Supreme (FS) and FS preheated (FSH). The film thickness (F) test (n=10) was done using two glass slabs under compression. Flexural strength (FLS) and modulus (FLM) were evaluated using a three-point flexion test (n=10). Polymerization shrinkage stress (PSS) was evaluated in a universal testing machine (n=5). Gap width (GW) between composite and mold was measured in internally polished metallic molds (n=10). The degree of conversion (DC) was evaluated by Fourier Transform Infrared spectroscopy (n=3). The morphology of the filler particles was checked by scanning electron microscope (SEM) and EDX analysis. Surface gloss (SG) and surface roughness (SR) were evaluated before and after mechanical brushing (n=10). The outcomes were submitted to 2-way ANOVAand Tukey's test (a=0.05). Lower mean values of F were observed for the preheated groups when compared to the non-preheated groups. URH and FSH showed higher mean values of FLS and FLM when compared with UR and FS. No differences were observed between groups in the PSS test. The GW was higher for the UR and FS groups when compared with URH and FSH. The DC was higher for preheated resin composites when compared to the non-preheated groups. The SR of the UR composite was higher than the FS after mechanical brushing, while the SG was higher for the FS groups. In conclusion, the universal resin composite tested generally presented similar physicochemical properties compared with the nanofilled resin composite and either similar or slightly inferior surface properties. The preheating improved or maintained all properties evaluated.
Keywords: dental materials; heating; nanoparticles; properties; Resin composite